Estudo dos fatores de risco cardiometabólicos e da função cardíaca em pacientes com acromegalia - OLIVEIRA, Marília Matos (2019)
TRODUCTION: Acromegaly is a rare disease, most commonly caused by a growth hormone-secreting pituitary macroadenoma. The diagnosis is based on findings such as enlargement of extremities and soft tissues, pan-hypopituitarism, neuroophthalmological symptoms and signs due to compression of adjacent structures as the tumor grows. It can be confirmed by increased concentrations of GH and insulinlike growth factor 1 (IGF-1), non-suppression of GH during oral glucose tolerance test (TOTG), and presence of tumor seen by magnetic resonance imaging of the Túrcica saddle. The treatment can be performed through surgery, medication and/or radiotherapy, with the aim of normalizing GH and IGF-1 concentrations and reducing disease-related morbidity and mortality. Among the complications associated with acromegaly, cardiovascular events are the most frequent. OBJECTIVE: To evaluate the presence and frequency of cardiometabolic risk factors, as well as the cardiac structure and function of patients with acromegaly at the Federal University of Triângulo Mineiro. MATERIAL AND METHODS: A total of 19 patients with acromegaly, aged 19-78 years (median: 58), 12 (63.2%) males and 7 (36.8%) females were analyzed; 16 healthy volunteers were selected as a comparative group, ranging from 24 to 72 years (median: 53), 9 (56.3%) males and 7 (43.8%) females. Clinical cardiometabolic risk markers (body mass index - IMC, Waistline - CA, systemic arterial pressure - PAS) and laboratory (glucose concentrations, glycated hemoglobin - HbA1C, insulin, Homa-IR index, uric acid, homocysteine, lipid profile, APO A, APO B) were determined in addition to concentrations of GH, IGF1, 250H-D and leptin. Heart function and structure were analyzed (aortic diameter (AO), left atrial diameter (AE), left atrial volume index (IVAE), left ventricular diastolic volume (VdVE) and final LV systolic volume (VsVE) , LV ejection fraction (FE), LV mass calculation [by the DEVEREUX formula according to the Pen Convention (1987)] (IMVE), interventricular septum thickness (SpVE), posterior wall septum (PpVE), initial velocity of the myocardium / left ventricle at the level of the mitral annulus (E'), ratio of initial mitral flow velocity with initial myocardial velocity (E/E') and cardiacvalvular study, determination of intima-media thickness - EMIC and presence or absence of plaques indicative of atherosclerosis. The echocardiogram variables were correlated with the presumed disease time and serum leptin concentrations. RESULTS: According to IMC, 14 patients were overweight / obese (73.7%); Five patients (26.3%) had diabetes mellitus and six (31.6%) pre-diabetes. Systemic arterial hypertension was present in 10 (52.6%) and 8 (42.1%) presented dyslipidemia. The mean IMC, CA, fasting glycemia, HbA1C and 250H-D were significantly higher among acromegalics than controls. According to concentrations of GH and IGF1, two subgroups, active disease (GH> 1ng / mL and IGF1 increased) and inactive (GH <1 ng / mL and normal IGF1) were formed. The inactive disease subgroup had significantly higher homocysteine concentrations than the control and total cholesterol, HDL-cholesterol, and non-HDL-c cholesterol groups in the control group. Acromegalic EMIC, inactive disease, was significantly higher in relation to the controls. In acromegalics there was a higher frequency of arrhythmias, valvulopathies, electrocardiographic alterations and echocardiographic findings were suggestive of acromegalic cardiomyopathy, especially IMVE, which was significantly higher in comparison to the comparative group. Correlation analyzes showed a direct correlation between IGF-1 and VsVE and between IGF-1 and VdVE in the acromegalic group and in the inactive disease subgroup. Cardiometabolic risk markers, analyzed for GH concentrations, showed a direct and significant correlation only with ferritin concentrations. There was a correlation between leptin and AO, and between leptin and VsVE in the active disease group. There was no correlation between echocardiographic variables and presumed disease time. CONCLUSION: Acromegalic patients presented altered clinical and laboratory markers in relation to the comparative group, expressed by increased adiposity indexes, higher frequency of glycemic and lipid alterations. In addition, heart structural changes were frequent, in relation to comparative group, even in individuals already treated and with inactive disease, justifying the increase in cardiovascular mortality described in the literature. These data suggest early and preventive actions of the most prevalent cardiovascular alterations, along with hormonal and metabolic control.